Pengaruh Penerapan Good School Governance Terhadap Pengelolaan Keuangan dengan Transparansi sebagai Variabel Moderasi pada Sekolah Dasar (SD) di Kabupaten Aceh Barat Daya - Azanna Fasalli; Zulkifli Umar; Hendri Mauliansyah (AKUNTANSI 45, 2025)
The purpose of this study was to test and analyze the effect of good school governance implementation on financial management moderated by transparency in Elementary Schools (SD) in Aceh Barat Daya District. Research data were collected through a list of questions/questionnaires and documentation studies. Hypothesis testing using Moderated Regression Analysis (MRA), simultaneous tests and partial tests are intended to determine simultaneously and partially the effect of independent variables on the dependent variable at a 95% confidence level (α = 0.05). The object of this research is about Good School Governance and Transparency and Financial Management (Elementary Schools (SD) in Aceh Barat Daya Regency). The sample size of this research is 74 respondents. The results of the study indicate that the implementation of good school governance has an effect on financial management in Elementary Schools (SD) in Aceh Barat Daya Regency. The implementation of good school governance has an effect and is significant on financial management moderated by transparency in Elementary Schools (SD) in Aceh Barat Daya Regency.